Does Price Discovery Process Hold during Post-COVID Period in Cryptocurrency? Evidence from Bitcoin - Sharma, Prashant; Kumar, C. T. Sunil; Singh, Pallavi; Satapathy, Debi Prasad; Sharma, Ashish (International Journal of Economics and Financial Issues, 2025)
With the introduction of derivatives contracts in the market, it is expected that these instruments will assist the markets with price discovery mechanism. The price discovery mechanism enables the spot market to assess the future expectations of the market by assessing the trends in the prices of futures contracts of underlying securities. Since the inception of derivative contracts on bitcoin in 2017, the derivative market has witnesses significant surge in overall trading volumes and turnover. With more contacts being traded in bitcoin futures, it becomes imperative to assess whether this is leading to price discovery process or not. The world has also witnessed the COVID-19 as black swan event in past few years and it is equally important to assess whether there is any impact of COVID-19 on the price discovery process in bitcoin market. In view of this, the present study tries to assess the impact of COVID-19 on price discovery process on bitcoin. The study considers the daily time series data of bitcoin and bitcoin future from 2017 to 2024 and applies standard time series econometrics methods including test of stationarity, Johnsen co-integration test, vector error correction mechanism and Wald test to assess the long-run and short-run causality between bitcoin spot and future contracts. The results of the study suggest that price discovery is taking place in bitcoin market and Covid-19 has no significant impact on the price discovery process in bitcoin.